The Integration of Judicial Review in Indonesia - Airlangga Gama Shakti; Maharani Wicahyaning Tyas; M. Lutfi Rizal Farid (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2022)
The judicial review is the essence of constitutional justice. At this time, Indonesia has adopted a dualism system in judicial review, which creates problems. This study aims to analyze the current judicial review system and examine the integration of judicial review by the Constitutional Court as ius constituendum. In reviewing the legal problems in this research, the Constitutional Court used the juridical-normative method. Furthermore, this research also uses a regulatory approach and a comparative study in Austria and Germany. The results show that Articles 24A and 24C of the Indonesia Constitutionhave delegated the Supreme Court the right to judicial review of regulations under the law, while the Constitutional Court has judicial review against the Indonesia Constitution. This raises problems, from practice to the difficulty of guarding the hierarchy of norms from Regional Regulations to the Indonesia Constitution. Judicial review at the Supreme Court also still has problems, especially transparency and accountability, because they have a closed nature. If analyzed in Austria, the Constitutional Court has the authority to judicial review the constitutionality of laws and the legality of administrative regulations (policies). In Germany, the Federal Constitutional Court has the authority to judicial review the law against the constitution. Therefore, there is a need for an urgency to integrate the judicial review by the Constitutional Court through the Amendment to the Indonesia Constitutionand several revisions to the regulations.